Age related axonal neuropathy in spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD). Issue 2 (1st February 1999) - Klockgether, Thomas; Schöls, Ludger; Abele, Michael; Bürk, Katrin; Topka, Helge; Andres, Frank; Amoiridis, Georgios; Lüdtke, Rainer; Riess, Olaf; Laccone, Franco; Dichgans, Johannes
Abstract : To identify determinants of peripheral involvement in spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD) the influence of CAG repeat length, age of onset, disease duration and age on the results of nerve conduction studies was analysed in 58 patients with SCA3/MJD. Patients with SCA3/MJD showed marked reduction of compound muscle action potential (CMAP) and sensory nerve action potential (SNAP) amplitudes indicating axonal neuropathy of both motor and sensory fibres. In addition, there was moderate slowing of nerve conduction suggestive of mild peripheral demyelination. Multivariate regression showed that CMAP and SNAP amplitudes decreased with age, but were not affected by CAG repeat length, age of onset, or disease duration. The age related decline of CMAP and SNAP amplitudes in SCA3/MJD was greater than in normal subjects. The data suggest that the degree of peripheral damage in SCA3/MJD does not depend on CAG repeat length, age of onset, or disease duration, but is mainly related to the time period over which the SCA3/MJD mutation exerts its effect.